Complementary Therapy in Overcoming Complaints During Menopause: A Literature Study - Agustina, Rama (Yayasan Ahmad Mansyur Nasirah, 2025)
Hormonal changes during menopause—particularly the decline in estrogen levels—often trigger a range of physical and psychological symptoms, including hot flashes, sleep disturbances, joint pain, mood swings, anxiety, and depression. This study aims to analyze complementary therapies that have been scientifically proven to alleviate menopausal symptoms. The research method employed is a literature review. Data were collected from peer-reviewed scientific articles published between 2018 and 2024, accessed through electronic databases such as PubMed, ScienceDirect, Scopus, ProQuest, and Google Scholar. Selected articles met the criteria of full-text availability and focused on complementary therapies for menopausal women. The findings indicate that therapies such as acupuncture, yoga, reflexology, aromatherapy, music therapy, and the use of herbal remedies (phytoestrogens) have demonstrated effectiveness in improving the quality of life for menopausal women. The conclusion is that complementary therapies offer significant potential in managing the physical and psychological symptoms associated with menopause. Their integration into holistic care approaches can enhance well-being and life quality in menopausal women. Future longitudinal studies are recommended to explore the sustained effects of complementary therapies on hormonal regulation, psychological health, and the risk of chronic diseases in menopausal populations. Additionally, clinical guidelines should be developed to standardize the use of these therapies in menopausal care.